1996
DOI: 10.1159/000109909
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neurological Disorders in a Japanese Town

Abstract: The prevalence of all neurological disorders in a Japanese town was calculated, with a result of 91.1 per 1,000 population. The prevalence of cerebrovascular disease was 28.8; myelopathy and/or radiculopathy caused by deformity of the spine or disc herniation, 23.9; neuralgia, 11.5; dementia, 10.4; peripheral nerve disturbance, 5.5; epilepsy, 4.4; Parkinson''s disease, 2.0; mental retardation, 2.9; brain/spinal tumor, 1.4; headache, 10.8, and vertigo/dizziness, 4.4. The prevalence of headache and vertigo/dizzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…Nakashima et al [2] conducted a postal survey in 1996 that reached 7,685 respondents, and concluded that dizziness affected 6.1% of them. Neuhauser et al [3] conducted a telephone survey in 2005 that reached 4,869 respondents, and concluded that 7.8% of the respondents suffered from dizziness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakashima et al [2] conducted a postal survey in 1996 that reached 7,685 respondents, and concluded that dizziness affected 6.1% of them. Neuhauser et al [3] conducted a telephone survey in 2005 that reached 4,869 respondents, and concluded that 7.8% of the respondents suffered from dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to define, impossible to measure, a challenge to diagnose and troublesome to treat. It is ranked among the most common complaints in primary care office practice, affecting approximately 6.1% -21% of the general population [1,2,3]. Its prevalence increases with age and may be as high as 30% in those over 65 years of age [4].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies inquired about dizziness in the last month with estimates of 15.8 (15) and 23% (1), with a figure of 10.9% experiencing dizziness severe enough to interfere with normal activities (1). The highest estimate of rate of dizziness is 85% over 18 months (16) and 59.2% over 12 months (17), and the lowest is 0.44% (18). However, this last study did not specify the time period over which respondents were required to report symptoms and so the figure is difficult to interpret meaningfully.…”
Section: Studies Of Dizziness As a Symptommentioning
confidence: 92%
“…12,13 In particular, number of patients with vestibular dysfunction reached 850,000, which mean 54% of increment from five years earlier(Previous studies reported that the prevalence of dizziness for 1 year ranged from 6.1% to 27%. 14,15 The prevalence or vestibular dysfunction has shown 35.4%…”
Section: Current State Of Dizziness and Rehabilitation In South Koreamentioning
confidence: 99%